Tinjauan Yuridis Penerbitan Sertifikat Atas Tanah Berdasarkan Putusan Pengadilan Karena para Pihak Tidak Diketahui Keberadaannya : (Studi Kasus Putusan Nomor: 5/Pdt.G/2024/Pn. Pct) - Sely Dwika Padila (CV Rewang Rencang, 2025)
This study examines the issuance of land title certificates based on court decisions when the parties are unknown. The main focus is Decree Number 5/Pdt.G/2024/PN Pct, which provides a legal basis for issuing certificates to buyers even though the seller cannot be contacted. The method used is a normative case approach. This study aims to analyze the legal provisions and procedures for the transfer of land rights through court decisions. The results of the study indicate that court decisions can be used as a legitimate basis for issuing certificates, providing certainty and legal protection for land owners.